Ventilation History of the Nordic Seas Deduced from Pelagic‐Benthic Radiocarbon Age Offsets - Telesiński, Maciej M.; Ezat, Mohamed; Muschitiello, Francesco; Bauch, Henning A.; Spielhagen, Robert F. (Geochemistry, Geophysics, Geosystems, 2021)
Changes in ocean circulation are considered a major driver of centennial-to-millennial scale climate variability during the last deglaciation. Using four sediment records from the Nordic Seas, we studied radiocarbon ventilation ages in subsurface and bottom waters to reconstruct past variations in watermass overturning. Planktic foraminiferal ages show significant spatial variability over most of the studied period. These differences suggest that the ventilation of the shallower subsurface waters is strongly influenced by local conditions such as sea-ice and meltwater input, changes in mixed-layer depth, and/or variable contributions of water masses with different 14 C signatures. Despite covering a significant water depth range, the benthic foraminiferal records show common long-term patterns, with generally weaker ventilation during stadials and stronger during interstadials. The Greenland Sea record differs the most from the other records, which can be explained by the greater depth and the geographical distance of this site. The benthic records reflect regional shifts in deep convection and suggest that the deep Nordic Seas have been generally bathed by a single, though changing, deep-water mass analogous to the present-day Greenland Sea Deep Water. Since significant offsets in ventilation ages are yielded by different taxonomic or ecological groups of benthic foraminifera, the use of uniform material seems a prerequisite to reconstruct bottom water ventilation histories.